Ginevra de Benci S Portrait: Had the Lady a Myopathic Face? - Lay-Son-Rivas, L (2012)
The portrait of Ginevra de Benci was painted by Leonardo da Vinci around 1474. This painting is less famous and less known than Mona Lisa but it is extremely captivating and interesting due to its own characteristics. The overall picture gives to the viewer the impression of being in front of an enigmatic, hermetic and introspective woman. However, some details of her facial expression, especially the gaze direction, the upper eyelids heaviness, the flat mouth and the absence of any defined emotion, give her the appearance of a patient with a muscular disease. © 2011 Springer-Verlag.